Thermally Activated Upconversion Near‐Infrared Photoluminescence from Carbon Dots Synthesized via Microwave Assisted Exfoliation. Issue 50 (13th November 2019) - Li, Di; Liang, Chao; Ushakova, Elena V.; Sun, Minghong; Huang, Xiaodan; Zhang, Xiaoyu; Jing, Pengtao; Yoo, Seung Jo; Kim, Jin‐Gyu; Liu, Enshan; Zhang, Wei; Jing, Lihong; et al.
Abstract: Upconversion near‐infrared (NIR) fluorescent carbon dots (CDs) are important for imaging applications. Herein, thermally activated upconversion photoluminescence (UCPL) in the NIR region, with an emission peak at 784 nm, which appears under 808 nm continuous‐wave laser excitation, are realized in the NIR absorbing/emissive CDs (NIR‐CDs). The NIR‐CDs are synthesized by microwave‐assisted exfoliation of red emissive CDs in dimethylformamide, and feature single or few‐layered graphene‐like cores. This structure provides an enhanced contact area of the graphene‐like plates in the core with the electron‐acceptor carbonyl groups in dimethylformamide, which contributes to the main NIR absorption band peaked at 724 nm and a tail band in 800–850 nm. Temperature‐dependent photoluminescence spectra and transient absorption spectra confirm that the UCPL of NIR‐CDs is due to the thermally activated electron transitions in the excited state, rather than the multiphoton absorption process. Temperature dependent upconversion NIR luminescence imaging is demonstrated for NIR‐CDs embedded in a polyvinyl pyrrolidone film, and the NIR upconversion luminescence imaging in vivo using NIR‐CDs in a mouse model is accomplished. Abstract : Thermally activated upconversion near‐infrared (NIR) photoluminescence is realized in NIR absorbing/emissive carbon nanodots (NIR‐CDs) with a single‐to‐few‐layer graphene‐like structure synthesized via microwave assisted exfoliation. A mechanism involving thermally activated electron transitions in the excited state is identified for the occurrence of the upconversion photoluminescence. Upconversion NIR luminescence imaging is demonstrated for NIR‐CDs.